English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

by what constant should one of the equations be multiplied if the x terms are drop out?

2006-12-04 03:10:19 · 6 answers · asked by styles4u 4 in Science & Mathematics Mathematics

6 answers

(-4x - 7y = 4 (.-6)
(-24x - 9y = -6
==>
You must equal the terms of "x" to cancel, multiplying Equation 1 to -6:
(24x + 42y = -24
(-24x - 9y = -6
Addition:
24x -24x + 42y - 9y = -30
33y = -30
y = -10/11

-4x -7(-10/11) = 4
-4x +70/11 = 4
-4x = 4 - 70/11
-4x = -26/11
x = -26/11 : -4
x = -26/11 . -1/4
x = 13/22
Solution: {(13/22; -10/11)}

2006-12-04 03:38:11 · answer #1 · answered by aeiou 7 · 1 0

In order to have the x-term cancel out when you perform the addition, the two terms must be equal and of opposite signs.

So multiply the first equation by -6 giving:
24x +42y =-24
Now when you add the second equation the x terms will disappear. [24x + (-24x) =24x-24x =0]

2006-12-04 11:25:54 · answer #2 · answered by ironduke8159 7 · 0 1

Your x terms are -4 and -24. To make them the same, you must multiply the first equation by -24/-4, which happens to be 6. Your first equation is now

-24x - 42y = 24

2006-12-04 11:15:37 · answer #3 · answered by fletchermse 2 · 0 1

I agree with the value of 6, except that I would multiply by -6 to solve by the addition method.

2006-12-04 11:21:14 · answer #4 · answered by kindricko 7 · 0 1

multiply the first equation by 6

-24x -42 y = 24 substract the second from this

you obtain -33y =30 y = -10/11

substituing this value you obtain x = -22/57

verify my calculations!

2006-12-04 11:23:16 · answer #5 · answered by maussy 7 · 0 1

multiply (1) by -6
24x+42y=-24
-24x-9y=-6
adding
33y=-30
dividing by 33
y=-30/33
simplifying
y=-10/11
similarly multiplying (1) by -9 and (2) by 7
36x+63y=-54
-168x-63y=-42
adding
-132x=-96
dividing by -132
x=-96/-132
=8/11

2006-12-04 11:20:31 · answer #6 · answered by raj 7 · 0 1

fedest.com, questions and answers